Membudayakan Literasi pada Anak di UPT SD N. 064034 melalui Program MBKM USU - Sitanggang, Vani; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
The loss of a reading culture is the most important cause, even a learning culture in schools is starting to disappear little by little, indeed the percentage of school children has increased with the government's compulsory education program but this does not necessarily improve the quality of education because even though every day the children go to school they have never studied, especially a low reading culture. School seems to be just a daily routine. Schools have a very important role in instilling a culture of reading and writing (literacy) in students. Therefore, each school must provide full support for the cultivation of a culture of reading and writing (literacy) in schools. Literacy culture itself has a relationship in fostering an interest in reading and writing in elementary school children. In cultivating an interest in reading and writing, a literacy culture is the most important key in realizing this interest. As a result, to foster an interest in reading and writing, several roles must be needed, such as infrastructure in schools, the community and parents. If the role is inadequate, it will have a negative impact on the continuation of a good literacy culture